Effect of silver nanoparticles on marine organisms belonging to different trophic levels. (October 2015) - Gambardella, Chiara; Costa, Elisa; Piazza, Veronica; Fabbrocini, Adele; Magi, Emanuele; Faimali, Marco; Garaventa, Francesca
Abstract: Silver nanoparticles (Ag-NPs) are increasingly used in a wide range of consumer products and such an extensive use raises questions about their safety and environmental toxicity. We investigated the potential toxicity of Ag-NPs in the marine ecosystem by analyzing the effects on several organisms belonging to different trophic levels. Algae ( Dunaliella tertiolecta, Skeletonema costatum ), cnidaria ( Aurelia aurita jellyfish), crustaceans ( Amphibalanus amphitrite and Artemia salina ) and echinoderms ( Paracentrotus lividus ) were exposed to Ag-NPs and different end-points were evaluated: algal growth, ephyra jellyfish immobilization and frequency of pulsations, crustaceans mortality and swimming behavior, and sea urchin sperm motility. Results showed that all the end-points were able to underline a dose-dependent effect. Jellyfish were the most sensitive species, followed by barnacles, sea urchins, green algae, diatoms and brine shrimps. In conclusion, Ag-NPs exposure can influence different trophic levels within the marine ecosystem. Highlights: Ag-NP effects were investigated in marine species at different trophic levels. Algae, cnidarians, crustaceans and echinoderms were exposed to Ag-NP suspensions. Acute and behavioral end-points were evaluated to detect Ag-NP toxicity. All end-points underlined a dose-dependent effect at any level of the trophic chain. Ag-NPs exposure influenced different trophic levels within the marine ecosystem.